Effect of surface mechanical attrition treatment on tribological behavior of AISI 2205 steel. (2020) - Joshi, Manoj D.; Kumar, Vikesh; Litoria, Aditya K.; Singh, Digvijay; Hosmani, Santosh S.
Abstract: In the present work, tribological behavior of surface mechanical attrition treated (SMAT) AISI 2205 steel was studied under dry and lubricated conditions using different loads. SMAT process parameters were optimized using the Taguchi technique for maximum output response of surface roughness. It was found that the SMAT process altered the surface morphology and microhardness of the steel. The surface roughness (Ra) was increased from 0.0173 µm to 0.1392 µm after SMAT. SMAT improved the hardness of the steel surface by ∼40%. XRD analysis confirmed the generation of ∼13% deformation-induced martensite (DIM) on the top surface layer. SMAT was effective in reducing the specific wear rate by ∼30% at 0.5 m/s sliding speed and 20 N normal applied load in dry condition. Minimum specific wear rates of 1.4 × 10 −4 and 1.2 × 10 −7  mm 3 /Nm were observed for the SMATed specimens in dry and lubricated conditions, respectively. The coefficient of friction (CoF) was increased from 0.52 for the non-SMATed specimen to 0.66 for the SMATed specimen in dry sliding condition. However, in the lubricated condition, the CoF of the non-SMATed specimen was 0.034, and it was increased to 0.048 after SMAT.